2008
DOI: 10.1111/j.1755-263x.2008.00029.x
|View full text |Cite
|
Sign up to set email alerts
|

Diminishing return on investment for biodiversity data in conservation planning

Abstract: It is generally assumed that gathering more data is a good investment for conservation planning. However, the benefits of additional data have seldom been evaluated by analyzing the return on investment. If there are diminishing returns in terms of improved planning, then resources might be better directed toward other actions, depending on their relative costs and benefits. Our aim was to determine the return on investment from spending different amounts on survey data before undertaking a program of implemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
152
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 141 publications
(162 citation statements)
references
References 39 publications
10
152
0
Order By: Relevance
“…Collecting more data on species locations takes time, and delaying conservation action to acquire more information can result in net conservation losses if habitat conversion is ongoing (e.g., Grantham et al 2008Grantham et al , 2009. The solution that is widely advocated and used is to instead ensure adequate representation of ''surrogates:'' species whose spatial distribution is well known, along with biophysical habitat variables that have been mapped (Margules and Sarkar 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Collecting more data on species locations takes time, and delaying conservation action to acquire more information can result in net conservation losses if habitat conversion is ongoing (e.g., Grantham et al 2008Grantham et al , 2009. The solution that is widely advocated and used is to instead ensure adequate representation of ''surrogates:'' species whose spatial distribution is well known, along with biophysical habitat variables that have been mapped (Margules and Sarkar 2007).…”
Section: Introductionmentioning
confidence: 99%
“…While it is important to consider the trade-offs between monitoring, research and management (Grantham et al, 2008;McDonald-Madden et al, 2010;Sutherland et al, 2011), our study has demonstrated that continuing to implement conservation actions over time without rigorous evaluation of their effectiveness is inefficient. Active adaptive management addresses these concerns by emphasizing the iterative feedback between implementation of management actions and assessment of their effectiveness, continuously improving knowledge on the bs_bs_banner Animal Conservation.…”
Section: Why Is Adaptive Management the Best Strategy Forward?mentioning
confidence: 99%
“…When measuring the conservation retention of Protea species in the South African landscape, GRANTHAM et al (2008) challenge the assumptions of BALMFORD & GASTON (1999) that biodiversity data are generally good value, Yet, whereas GRANTHAM et al 's (2009) study site in the Fynbos may not require years and years of ongoing inventory, their results still emphasise the need to conduct good, detailed baseline surveys (optimal 1 year surveying length for their study site) before effective conservation management can ensue. Whilst the IPA surveys in the Arabian Peninsula represent a good starting point for identifying priority sites for plant conservation, the week long surveys of a site such as Jibal Qaraqir is insufficient to provide the data required to meet the GSPC Targets under Objective 2.…”
Section: Funding For Data Collectionmentioning
confidence: 99%